Archaeology of Oceania : Australia and the Pacific Islands - Lilley, Ian (Blackwell studies in global archaeology, 2006)
This book is a state-of-the-art introduction to the archaeology of Oceania. It is the first such text to provide integrated treatment of the archaeologies of Australia and the Pacific Islands, enabling readers to form a coherent overview of cultural developments across the region as a whole. The book brings together twenty-six of the region 's leading scholars to address a wide range of questions, ranging from the deep pulses of the longue dur ée to contemporary postcolonial realpolitik. All the contributions discuss current theoretical perspectives and take account of the most recent research data. This volume is essential reading for all those studying the Australasian and Pacific region.